TGF-β1 stimulation and VDR-dependent activation modulate calcitriol action on skeletal muscle fibroblasts and Smad signalling-associated fibrogenesis - Ratchakrit Srikuea; Muthita Hirunsai (Scientific Reports, 2023)
Abstract Fibroblasts play a pivotal role in fibrogenesis after skeletal muscle injury. Excess fibrous formation can disrupt contractile functions and delay functional recovery. Although vitamin D receptor (VDR) is expressed explicitly in regenerating muscle compared with uninjured muscle, how calcitriol [1α,25(OH)2D3] directly regulates skeletal muscle primary fibroblast proliferation, the transition to myofibroblasts, and Smad signalling-associated fibrogenesis is currently unknown. Herein, the effects of calcitriol on cultured skeletal muscle primary fibroblasts of male C57BL/6 mice (aged 1 month old) were investigated. The percentage of BrdU+ nuclei in primary fibroblasts was significantly decreased after calcitriol treatment; however, the antiproliferative effect of calcitriol was diminished after TGF-β1 stimulation to induce fibroblast to myofibroblast transition. This suppressive effect was associated with significantly decreased VDR expression in TGF-β1-treated cells. In addition, Vdr siRNA transfection abolished the effects of calcitriol on the suppression of α-SMA expression and Smad2/3 signalling in myofibroblasts, supporting that its antifibrogenic effect requires VDR activation. Compared with calcitriol, the antifibrotic agent suramin could inhibit fibroblast/myofibroblast proliferation and suppress the expression of TCF-4, which regulates fibrogenic determination. Collectively, these findings suggest that profibrotic stimulation and VDR-dependent activation could modulate the effects of calcitriol on skeletal muscle fibroblast proliferation and fibrogenesis processes. Therefore, TGF-β1 and VDR expression levels are crucial determinants for the antifibrogenic effect of calcitriol on skeletal muscle after injury.